SISTEM INFORMASI JADWAL PENERBANGAN PESAWAT BERBASIS WEB PADA CV. DIRGA ADI DHARMA - Purwanto, Hari (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2017)
In modern times at the present time, the development of airplane flight schedules in the world is growing rapidly. This can be seen with the increasing number of airplane schedules in the world using the website as a tool to view the flight departure schedule information and scheduled flight arrives. And the flight schedule of this online flight gets a lot of attention from the public who see the information through the flight schedule of the aircraft online. Many passengers have to come to the airport just to see the flight schedule, even sometimes there is no renewal schedule from the airport. This of course carries the impact of loss because the time spent on seeing information can be more effective. The authors hope with the existence of this information system, providing convenience for airplane passengers to monitor the schedule.